(untitled) (Medical Forum Monthly, 2020)
Objective: To Compare the efficacy and cost effectiveness of prostaglandin E2 with misoprostol 25 mcg for labour induction at term pregnancy. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Gajju Khan Medical College Swabi in six months from January 2019 to June 2019. Materials and Methods: Total 120 subjects were included in this study. These patients were divided in two groups. Group-1 and Group- 2. Group-1 was induced with PGE2, 3 mg tablets maximum of 2 doses, 6 hours apart. Group-2 induced with misoprostol 25 mcg 4 hourly, 4 doses. The subjects were full term pregnant women who were primigravida, 2nd or 3rd gravid and had bishop score less than 5. Results: The patients included in the study were between the ages of 20 to 40 years. The mean age of patients was 31.35±5.82 in both groups (p value > 0.05). All the patients in both groups were between 37 to 42 weeks of gestation. The mean gestational age of group-1 and group-2 was 39.23±1.46 weeks and 39.08±1.60 weeks (p > 0.05) respectively. Mean duration of labor in group 1 was 7.8±3.81 hours whereas in group 2, it was 6.50±3.35 hours. Oxytocin injection was given in 55% (33) patients in group 1 and 43.33% (26) in group 2. 25 % (15) patients in group 1 and 15 % (9) in group 2 were having duration of labor more than 10 hours. Conclusion: Misoprostol (PGE1 analogue) is a potent drug for labour induction with a short induction delivery interval and reduced need for Oxytocin augmentation. There is less rate of instrumental delivery and caesarean section and a reduced failure rate of induction with misoprostol.